2016
DOI: 10.1016/j.jveb.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability and predictive validity of a juvenile guide dog behavior test

Abstract: 14The ability to measure stable and consistent behavioral traits in dogs would facilitate 15 selection and assessment of working dogs, such as guide dogs. Ideally, these measures 16 should predict suitability for the working role from a young age. This study assessed test-17 retest reliability of a juvenile guide dog behavior test and predictive validity using 18 qualification or withdrawal from guide dog training. Ninety-three guide dog puppies (52F; 19 41M) were tested at 5 (mean 4.78; ± 0.73 SD) and 8 (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 48 publications
(2 reference statements)
5
66
0
Order By: Relevance
“…Similarly, dogs with shorter latencies to vocalize during the novel object task, a likely sign of higher anxiety (69), were more likely to be released from the program. This result is consistent with the findings of Harvey et al (26), who found that the guide dogs predicted to be successful had lower scores on a fear/anxiety PC at 5 mo of age. The component was partially based on vocalizing during tasks.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, dogs with shorter latencies to vocalize during the novel object task, a likely sign of higher anxiety (69), were more likely to be released from the program. This result is consistent with the findings of Harvey et al (26), who found that the guide dogs predicted to be successful had lower scores on a fear/anxiety PC at 5 mo of age. The component was partially based on vocalizing during tasks.…”
Section: Discussionsupporting
confidence: 92%
“…success is associated with high levels of obedience and trainability and low levels of reactivity, hyperactivity, aggression, distraction, and anxious behaviors (e.g., barking) (24,26,29,32,35). To date, however, no study has examined the direct effect of mother-puppy interactions on program success or failure; examined the direct effect of performance on cognitive tests on subsequent working dog success; or simultaneously explored maternal, cognitive, and temperament effects within the same model, thereby testing each variable while controlling for the others.…”
Section: Significancementioning
confidence: 99%
“…Correlations ranged from 0.42 to 0.69, whereas the meta-analysis found mean correlations of 0.34 for puppies and juveniles (<12 months of age) and 0.53 in adult dogs (>12 months of age)[26]. The strength of the correlations from this questionnaire completed by trained dog handlers also compares favourably to similar questionnaires completed by dog carers (correlations 0.25 to 0.56 [31] and 0.18 to 0.66 [10]). The lower end of correlations found here was higher than that found in the questionnaires scored by carers, a result which would be expected if trained dog handlers were more reliable/consistent in their evaluations, although inter-rater reliability was not possible to assess due to there being only one handler per dog.…”
Section: Discussionmentioning
confidence: 81%
“…Each prediction used a scale score from the questionnaire (a 0-100mm continuous measure) as the dependent variable, with behavioural coding measures from the juvenile guide dog behaviour test [10] as independent variables (IV’s). The predictions were based on the shared areas of behaviour the test and questionnaire were designed to assess.…”
Section: Methodsmentioning
confidence: 99%
“…The associated contributed papers suggest that these are all rich intellectual fields. Harvey et al (2016) present the results of early testing using a novel evaluation paradigm for dogs intended to become guide dogs. All working dogs require extensive, expensive training.…”
Section: Accepted Manuscriptmentioning
confidence: 99%